The Relevance of Tarbawy's Tafsir Values in Student Character Education - Tati Kurniawati; Iskandar Mirza (Penerbit Hellow Pustaka, 2024)
Tafsir Tarbawy is closely related to student character education at school. Values such as piety, honesty, responsibility, and respect can be included in the character education curriculum through a values-based learning approach, participation in extracurricular activities, and role models provided by teachers. With the application of these values, it is hoped that a generation will be formed that will not only excel academically, but also have good character, so that it can have a positive impact on society. Character education is an important aspect in the process of forming students' personalities, which aims to instill moral, ethical and social values. As an approach to the Quran that focuses on educational aspects, tarbawy interpretation plays an important role in this effort. This research aims to explore the relationship between tarbawy interpretive values and student character development in schools. Through a study of verses from the Qur'an that contain educational messages, this research found that values such as piety, honesty, responsibility and respect have an important role in shaping students' positive behavior, so that they can become the basis for the character education system in Indonesia.